Activity In The Middle Of The Company - Mhd Razaq's blessing; Lasminar Sihombing (Proceeding International Seminar of Islamic Studies, 2019)
Da'wah is not just limited to oral activities, but Da'wah can be done by an institute or company that includes all verbal activities and actions of one company that often performs Da'wah activities is a company. This study aims to determine and analyze how the da'wah activities carried out at the company in increasing the devotion of accountant employees. This study uses a qualitative approach to the type of case study research. Data collection techniques used were observation, interviews, and documentation. The results of this study show that the da'wah activities carried out by the company by carrying out the chase every week on Friday, in addition to the company doing special recitation in the month of Ramadan, as well as carrying out celebrations of religious holidays. The material delivered at the time of the recitation took place that is different every week. With the study of the company, it will increase the devotion of each employee, especially in the field of accountant.